A Geospatial Analysis of Disclosure of and Social Reactions to Sexual Victimization on Twitter Using #MeToo. Issue 3 (2nd October 2021) - W. Bogen, Katherine; M. Orchowski, Lindsay
Abstract: Twitter has emerged as a space for survivors of sexual violence to share unwanted sexual experiences and for web users to provide support and feedback. Because Twitter data is often associated with latitude and longitude points, geospatial mapping of tweets that utilized the hashtag #MeToo to discuss experiences of sexual violence may be useful in understanding ways to best deliver resources to survivors who seek help online. Accordingly, the present study conducted an exploratory geographic information systems (GIS) "hotspot" (i.e., special cluster of tweet events) analysis to examine the feasibility of mapping tweets including the hashtag #MeToo with associated latitude and longitude data ( N  = 777) to target interventions and resource provision. Data indicated that tweets with the hashtag #MeToo were dispersed across the United States in a manner inconsistent with population density and that concentrated points emerged in other countries. Data suggest that certain geographic regions are more motivated to discuss sexual violence online and are perhaps in more dire need of violence-related resources. Future research should incorporate GIS analysis of larger Twitter datasets to target resource provision toward populations engaged in help-seeking online. GIS analysis of Twitter discourse surrounding gender-based violence may also be utilized by law enforcement, healthcare agencies, and academicians to develop targeted interventions.